2012
DOI: 10.1186/1472-6882-12-156
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by curcumin of multiple sites of the transforming growth factor-beta1 signalling pathway ameliorates the progression of liver fibrosis induced by carbon tetrachloride in rats

Abstract: BackgroundAt present there is no effective and accepted therapy for hepatic fibrosis. Transforming growth factor (TGF)-β1 signaling pathway contributes greatly to hepatic fibrosis. Reducing TGF-β synthesis or inhibiting components of its complex signaling pathway represent important therapeutic targets. The aim of the study was to investigate the effect of curcumin on liver fibrosis and whether curcumin attenuates the TGF-β1 signaling pathway.MethodsSprague–Dawley rat was induced liver fibrosis by carbon tetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 45 publications
5
69
0
Order By: Relevance
“…31 Our data demonstrate that the upregulation of TGF-b was associated with increased phosphorylation of Smad3, effects which were partially abrogated by melatonin. These results similar to those previously reported in rats treated with CCl 4 for asiatic acid, a natural product from Centella asiatica, 32 and curcumin 30 suggest that restoring the balance of TGF-b/Smad signaling may be a central mechanism by which melatonin inhibits liver fibrosis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…31 Our data demonstrate that the upregulation of TGF-b was associated with increased phosphorylation of Smad3, effects which were partially abrogated by melatonin. These results similar to those previously reported in rats treated with CCl 4 for asiatic acid, a natural product from Centella asiatica, 32 and curcumin 30 suggest that restoring the balance of TGF-b/Smad signaling may be a central mechanism by which melatonin inhibits liver fibrosis.…”
Section: Discussionsupporting
confidence: 90%
“…36 It has been reported that in rats treated with CCl 4 silymarin decreases CTGF to improve liver fibrosis 37 and curcumin significantly attenuates the severity of liver damage through inhibition of CTGF expression. 30 Our findings confirmed that chronic CCl 4 administration markedly enhanced the intrahepatic expression of CTGF mRNA and protein, and that melatonin significantly reduced these CCl 4 -induced increases.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…17 Twenty rats were randomly divided into two groups. Rats in Group 1 (n = 10) received twiceweekly injections of olive oil (vehicle control) while those in Group 2 (n = 10) received twice-weekly injections of CCl 4 plus oral PBS (CCl 4 -treated rats).…”
Section: Liver Injury Modelmentioning
confidence: 99%
“…4 Multiple studies in both animals and human indicated that curcumin possesses a variety of potent properties, including antioxidant, antiÀinflammation, radicalÀscavenging, anticancer, and so on. 5,6 Several studies indicated that curcumin can suppress the proliferation of leukemia and induce cell death. [7][8][9] Besides, it shows no significant side effects compared with other chemotherapeutic drugs.…”
Section: Introductionmentioning
confidence: 99%